2004
DOI: 10.1037/0022-006x.72.2.328
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Course, and Predictors of Emotional Distress in Pregnant and Parenting Adolescents.

Abstract: This study examines trajectories and correlates of emotional distress symptoms in pregnant adolescents (n = 203) and nulliparous adolescents (n = 188) from economically disadvantaged communities over an 18-month period. For both groups, the prevalence of significant emotional distress exceeded expectation based on adolescent norms; however, the severity of symptoms did not differ between the 2 groups. Results from growth curve modeling revealed a significant decline in symptoms during the study period for both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 51 publications
4
64
0
Order By: Relevance
“…However, recent research found no differences between the adjustment levels of these adolescents and those of their peers who had the same socioeconomic conditions (Milan et al 2004;Troutman and Cutrona 1990). Additionally, some studies reported nonclinical levels of emotional maladjustment (Sieger and Renk 2007) for pregnant adolescents, who in some cases presented better results when compared with their peers without a pregnancy history (Pires 2009), as well as similar results in relational adjustment (Araújo Pedrosa 2009).…”
Section: Adjustment During Pregnancymentioning
confidence: 96%
See 3 more Smart Citations
“…However, recent research found no differences between the adjustment levels of these adolescents and those of their peers who had the same socioeconomic conditions (Milan et al 2004;Troutman and Cutrona 1990). Additionally, some studies reported nonclinical levels of emotional maladjustment (Sieger and Renk 2007) for pregnant adolescents, who in some cases presented better results when compared with their peers without a pregnancy history (Pires 2009), as well as similar results in relational adjustment (Araújo Pedrosa 2009).…”
Section: Adjustment During Pregnancymentioning
confidence: 96%
“…Finally, regarding social factors, low socioeconomic levels (Jaffee et al 2001;Milan et al 2004) appear to be associated with poor socioemotional adjustment. However, the results of recent national and international investigations (Araújo Pedrosa 2009;Logsdon et al 2008;Van Horne et al 2009) grounded on the bioecological model of development (Bronfenbrenner and Ceci 1994) revealed that factors from multiple ecological levels interact and affect different areas of adolescents' adjustment after pregnancy, reinforcing the importance of theory-based research to capture the maximum variability in the dependent variables studied.…”
Section: Adjustment During Pregnancymentioning
confidence: 97%
See 2 more Smart Citations
“…Adolescent parents might experience significant emotional distress from issues such as perceived parenting criticism, inadequate partner support, intimate partner violence, and financial resource strain [24,47,48]. Such distress might impair the establishment of the parentechild relationships leading teen parents to have less confidence in their own parenting abilities and even less acceptance of their own children [49].…”
Section: Adolescent Parenting In the Neonatal Intensive Care Unitmentioning
confidence: 99%